Race, Gender, and Chains of Disadvantage: Childhood Adversity, Social Relationships, and Health. (March 2014) - Umberson, Debra; Williams, Kristi; Thomas, Patricia A.; Liu, Hui; Thomeer, Mieke Beth
We use a life course approach to guide an investigation of relationships and health at the nexus of race and gender. We consider childhood as a sensitive period in the life course, during which significant adversity may launch chains of disadvantage in relationships throughout the life course that then have cumulative effects on health over time. Data from a nationally representative panel study (Americans' Changing Lives, N = 3, 477) reveal substantial disparities between black and white adults, especially pronounced among men, in the quality of close relationships and in the consequences of these relationships for health. Greater childhood adversity helps to explain why black men have worse health than white men, and some of this effect appears to operate through childhood adversity's enduring influence on relationship strain in adulthood. Stress that occurs in adulthood plays a greater role than childhood adversity in explaining racial disparities in health among women.